Improving Batik and Dropship SMEs Market through Geographic Information System - Agus Ilyas; Sattriedi Wahyu Binabar; Tri Agus Setiawan; Paminto Agung Christianto (Universitas Kristen Satya Wacana, 2023)
The information providing about dropship, Small and Mid-size enterprise (SMEs), in Pekalongan city recently is done by brochure, banner and social media. Nevertheless, other than social media, the promotion media is possible to be seen when visitor is on the spot. The research is aimed at supporting the troubleshooting matters by adapting the Geographic Information System (GIS) in mapping about Batik SMEs dropship in Pekalongan city. The web based GIS will ease the market player, tourists or visitors as well as the society to get such information about dropship, SME centre and Batik market. The providing of web based GIS in informing the dropship, SME centre and Batik market in Pekalongan city is expected to give positive impact to Batik businessmen and to improve the economic rate in Pekalongan city.